Konflik Batin Tokoh Utama Dalam Film Serdadu KumbangKarya Jeremias Nyangoen: Tinjauan Psikologi SastraDan Implementasinya Sebagai Bahan Ajar Sastra Di SMA - Adeliya Anggraeny, Yolanda (2016)
This research aimed at: (1) describing the social-historical background of the writer Jeremias Nyangoen and his works, (2) describing the building structure of the movie 'Serdadu Kumbang', (3) describing the inner conflict in the main actor of the movie 'Serdadu Kumbang' studied from a literary psychology. (4) implementing the inner conflict into the literary learning in Senior High School. This research used a qualitative descriptive method. The subject of the research was the movie 'Serdadu Kumbang' and the object of the research was the inner conflict of the movie 'Serdadu Kumbang'. Data of the research were conversations in the movie 'Serdadu Kumbang'. The techniques of data collection were library technique, observing, and taking a note. The technique of data analysis used the reading of semiotic model consisting of the heuristic reading and the hermeneutic reading. The results of this research had four results: (1) Jeremias Nyangoen was born in Pontianak on 29 June 1968. His works are, among other: Kanibal - Sumanto, Di Timur Matahari, Denias, Senandung di Atas Awan; (2) the structural anaylisis: the theme of the movie 'Serdadu Kumbang' is the struggle of a child and friends to reach their dreams. The actors of this movie are: Amek, Umbe, Acan, Guru Imbok, Siti, Zakaria, and Minun. The plot used is a chronological plot. The settings of this movied were divided into three: setting of place, setting of time, and social setting; (3) from the results of analysis, it was found an inner conflict in the main actor of the movie 'Serdadu Kumbang'. The inner conflict consisted of three conflicts: approaching-approaching conflict, approaching-staying away conflict, and staying away-staying away conflict; (4) the results of the research could be implemented into the literary learning in Senior High School class XI semester II with the Core Competence: 3 Understanding, implementing and analyzing the factual, conceptual, procedural, and meta-cognitive knowledges based on their curiosity on knowledge, technology, artand- culture, and humanities with the insights of humanity, nationality, and civilization related to the phenomenon and incident, and implementing the procedural knowledge on the specific study field based on Their talent and interest to solve problems. Basic Competence: 3.3 Analyzing the movie/play review either orally or in written. Based on the analysis of the movie 'Serdadu Kumbang', the inner conflict of the main actor could be made as a good model for the students that limitation can be defeated by motivation of never giving up and the persistence in reaching the goal.